2020
DOI: 10.3390/nu12051237
|View full text |Cite
|
Sign up to set email alerts
|

Legume Consumption Patterns in US Adults: National Health and Nutrition Examination Survey (NHANES) 2011–2014 and Beans, Lentils, Peas (BLP) 2017 Survey

Abstract: Given the emerging health benefits of regular legume consumption, we hypothesized that the historically low legume consumption levels in US adults increased. We evaluated legume consumption patterns in US adults using cross-sectional data from the 2011–2012 and 2013–2014-year cycles of National Health and Nutrition Examination Surveys (NHANES) and a 2017 cross-sectional, online survey of Oregon families named “Beans, Lentils, Peas (BLP) Survey”. We also compared legume consumption patterns between consumers be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
26
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 17 publications
2
26
2
Order By: Relevance
“…Sodium intake was assessed in Canada only, and consumers of pulses had a higher sodium intake compared to non-consumers [ 58 ], in agreement with our results. However, conversely to our study in which individuals with an adequate diet for pulses were mostly men, gender was not associated with the consumption of pulses in other countries [ 58 , 59 , 60 , 61 ].…”
Section: Discussioncontrasting
confidence: 99%
“…Sodium intake was assessed in Canada only, and consumers of pulses had a higher sodium intake compared to non-consumers [ 58 ], in agreement with our results. However, conversely to our study in which individuals with an adequate diet for pulses were mostly men, gender was not associated with the consumption of pulses in other countries [ 58 , 59 , 60 , 61 ].…”
Section: Discussioncontrasting
confidence: 99%
“…Results showed an increase for the subcategory, but was attributable to increases in nuts and seeds and not legumes. In a more recent study using NHANES 2011–2014, 2-day median intake of pulses were the same across the 4-year period [ 17 ]. The only other evidence that intakes of legumes or pulses have changed very little are general reports on WWEIA, and NHANES data that compared total vegetable intake, which includes legumes, in 2003–2004 and 2015–2016 [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…This study also revealed that people with a self-reported diagnosis of depression who never or hardly ever consumed legumes had also decreased. For example, when legume consumption decreased among US adults, improved communication about their benefits was introduced [ 111 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is vital for health authorities to take these findings into consideration when designing strategies to improve diet quality among individuals with depression. Although this research showed that the number of people who never or hardly ever consumed legumes and people who consumed soft drinks with sugar on a daily basis declined from 2011 to 2017, government agencies should persevere with their efforts to reduce the consumption of soft drinks with sugar due to its potential dangers for general health [ 117 ] and encourage people to consume more legumes for their health benefits [ 111 ]. Additionally, our findings of depressive people suggest that males, people aged 16–24 years old and 25–44 years, separated or divorced, and also smokers were more likely to have a poor or improvable diet quality.…”
Section: Discussionmentioning
confidence: 99%